Training Programs for Paramedics’ First Aid Competence in Traffic Accidents: Program Pelatihan untuk Kemampuan Pertolongan Pertama Paramedis dalam Kecelakaan Lalu Lintas - Sadoon, Hajar Haider (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Road traffic accidents are a major cause of global mortality and disability. Specific Background: Limited prehospital care and inadequate paramedic skills worsen trauma outcomes, particularly in Iraq and similar regions. Knowledge Gap: Evidence on the effectiveness of structured training programs for paramedics in first aid procedures is fragmented. Aim: This review critically appraises studies from 2014–2024 evaluating training programs to enhance paramedics’ competencies in managing road traffic injuries. Results: From 17,000 records, 7 high-quality studies were included, covering cardiopulmonary resuscitation, bleeding control, aeromedical evacuation, tactical combat casualty care, and trauma management. Most programs showed significant improvements in knowledge and skills, with simulation-based and video-assisted training being most effective. Novelty: This is the first synthesis focused on paramedics’ first aid training for road accidents in Iraq and comparable settings. Implications: Ongoing, evidence-based training programs are essential to reduce preventable deaths and improve emergency response capacity.Highlight : Highlights the impact of training programs on improving paramedics’ first aid skills. Emphasizes the role of continued education in reducing mortality and disabilities. Identifies effective teaching methods like simulation and video-assisted learning. Keywords : First Aid, Pre-hospital Care, Training Programs, Road Traffic Accidents, Paramedics' Competencies